THE CURRENT STATE OF SCIENTIFIC DEVELOPMENTS IN THE FIELD OF PUBLIC ADMINISTRATION OF COUNTER-RAIDING - Velychko L. Yu.; Kuzmenko T. M. (Pressing Problems of Public Administration, 2021)
The content of dissertations and professional publications dedicated to counteracting corporate raiding has been analysed. The insufficiently elaborated aspects of public administration of counteraction to corporate raiding are highlighted as the subject of proprietary dissertation research.An important prerequisite for the development of a national economy is the strengthening of its resource potential, which in turn is subject to additional investments. However, the interest in these processes does not only depend directly on the profitability of a certain type of business but also the protection of assets from raiders. Despite the government’s promises and initiatives of the members of parliament, to this day, the general public occasionally receives information about an attempted raider takeover of a “stand-by” enterprise. This disappointing situation originates from shortcomings in the activities of the public authorities as well as potentially a lack of proper scientific justification of the counter-raiding mechanisms. All the above-mentioned determines the relevance of the given research.The problem of counteraction to corporate raiding has become a cornerstone in a number of dissertation studies and scientific publications by representatives of various fields of knowledge: 05 Social and behavioural sciences, 07 Management and administration, 08 Law, 28 Public administration and management, etc. In spite of this, there is still a lack of comprehensive research on the subject.The article aims to review the current state of scientific developments in the public administration of counter-raiding. The achievement of this goal entails the following tasks: 1) to analyse the content of dissertations and professional publications devoted to counteracting corporate raiding; 2) to highlight the underdeveloped aspects of public administration of counteracting corporate raiding as the subject of proprietary dissertation research.The starting point is dissertation research and professional publications of leading scientists who have investigated the peculiarities of counter-raiding. A comprehensive approach was used that involved the following empirical and theoretical methods: abstract-logical – for theoretical generalisations and the formation of conclusions; analysis and synthesis – to determine the factors affecting the nature and direction of public administration; comparative analysis – to study the developments of leading domestic scientists focused on the features of public administration to counteract corporate raiding.Domestic scholars have mainly focused on the following: clarifying the meaning of the concept of “raiding”; systematising the types of raiding; investigating the nature and root causes of raiding; assessing the risk of raiding; characterising the individual features of the stages of raiding; systematising the mechanisms (methods, means) of raiding; considering the dynamics of the spread of raiding; describing the impact of raiding on the national economy as a whole, its individual sectors / areas, markets and enterprises; identification of problems that reduce the effectiveness of counter-raiding; development of the concept of corporate raid prevention; highlighting the best international practices of corporate raid prevention; development of recommendations to minimise the risk of raider seizure and methods of protection against raiders; the need to improve individual mechanisms to combat raiding. Continued scientific research on this topic will contribute to improving the protection of business entities from raider attacks, including by improving the methodological basis for public administration in this area.